Isolamento e identificação de bactérias gram negativas no leite cru e pontos críticos de contaminação - Simões, Gilberto Henrique (2014)
The complexity and diversity of the dairy production chain in the country are due to the different types of dairy production systems and their specific characteristics, among them, the spatial and cultural differences found across the country, making it difficult to standardize the production, planning, technicization and especially the microbiological quality of the raw material in the dairy chain. In order to illustrate the dairy production systems, the managements, critical points of contamination, isolation and identification of the main factors involved in the contamination in Marechal Cândido Rondon - PR, some experiments were conducted. Initially it was performed a selection among 735 dairy production systems for semi - structured guides (production characteristics and general management) and cluster analyzes, which formed five distinct and homogeneous groups of dairy production systems. Only 10% of properties were selected to represent each group, totalizing 73 properties. Subsequently it was analyzed the milk cooling tanks for the somatic cell count (SCC) and total the bacterial count (TBC). After the counts, only 35 properties were selected for the research because they showed contaminations rates above current limits for SCC and TBC according to the MAPA regulation (IN 62). After the formation of the systems, collections related to the research were made, which consisted of the semi-structured questionnaire guide (hygienic-sanitary management), milk collection of the tank and swabs of critical points of contamination in milk production (hand of the milker, milking machine and cooling tank). The experiment was proceeded with microbiological analysis and quantification of Staphylococcus sp, hand of the milker, milking machine, tank and milk 9.6 x103, 2.2 x104, 1.4 x104 and 3.8 x103 CFU/mL respectively, and quantification, isolation and identification of proteolytic and lipolytic bacterias, in which the agents of highest incidence were Escherichia coli, Escherichia fergusoni, Yersinia enterocolitica and Klebsiella oxytoca both with 8.6% frequency in the different dairy production systems studied